Women of the Harlem renaissance - Wall, Cheryl A. (Women of letters (Bloomington, Ind.), 1995)
Features chapters on Jessie Redmon Fauset, Zora Neale Hurston and Nella Larsen. Also discusses other artists including Josephine Baker, Gwendolyn Bennett, Georgia Douglas Johnson, Charlotte Mason, Bessie Smith, Anne Spencer, and Jean Toomer.